Serum neurofilament light chain as a severity marker for spinocerebellar ataxia - Hye-Rim Shin (Nature Portfolio, 2021)
Abstract Since the serum neurofilament light (NfL) chain is known as a promising biomarker in neurodegenerative diseases, we aimed to evaluate serum NfL as a biomarker indicating neuronal damage in autosomal-dominant (AD) spinocerebellar ataxia (SCA). We reviewed patients diagnosed with AD SCA in the outpatient clinic of Seoul National University Hospital’s (SNUH) Department of Neurology between May and August of 2019. We reviewed the demographic data, clinical characteristics, Scale for the Assessment and Rating of Ataxia (SARA) score, and brain magnetic resonance imaging (MRI) scans. The serum NfL was measured by electrochemiluminescence (ECL) immunoassay. Forty-nine patients with AD SCA were reviewed and their serum NfL level was determined. The median serum NfL level (109.5 pg/mL) was higher than control (41.1 pg/mL) (p-value < 0.001). Among the AD SCA patients, there was a positive correlation between the serum NfL level and the trinucleotide repeat number (r = 0.47, p-value = 0.001), disease duration (r = 0.35, p-value = 0.019), disease duration/age × trinucleotide repeat number (r = 0.330, p-value = 0.021), and SARA score (n = 33; r = 0.37, p-value = 0.033). This study shows that serum NfL is elevated in AD SCA patients and correlates with clinical severity.